solHMK6 - Section 3.4 #4) (a) x n = 1- (- 1) n + 1 /n . We...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 3.4 #4) (a) x n = 1- (- 1) n + 1 /n . We take the subsequence of the even-indexed terms: x n k = x 2 k = 1- (- 1) 2 k + 1 / (2 k ) = 2 + 1 / (2 k ). So ( x 2 k ) converges to 2. Next we take the subsequence of odd-indexed terms: x 2 k- 1 = 1- (- 1) 2 k- 1 + 1 / (2 k- 1) = 1 / (2 k- 1). So ( x 2 k- 1 ) converges to 0. Since there are two subsequences converging to different limits, the entire sequence diverges. (b) x n = sin( n/ 4). We first take the subsequence of multiples of 8: x 8 k = sin(8 k/ 4) = sin(2 k ) = 0. So the subsequence ( x 8 k ) converges to 0. Now we take the subsequence where n k = 8 k + 2: x 8 k +2 = sin((8 k + 2) / 4) = sin(2 k + / 2) = sin( / 2) = 1. So ( x 8 k +2 ) converges to 1. Since there are two subsequences converging to different limits, the entire sequence diverges. #6) (a) x n +1 < x n ( n + 1) 1 / ( n +1) < n 1 /n ( n + 1) n < n n +1 ( n + 1) n n n < n 1 + 1 n n < n It was shown in Example 3.3.6 that (1+1 /n ) n < 3. Hence, for n 3, we have (1+1 /n ) n < 3 n , and therefore x n +1 < x n for all n 3. Thus, the sequence is ultimately decreasing (its 3-tail is decreasing) and since it is bounded below by 1, x := lim( x n ) exists. Also x 1. (b) ( x 2 n ) also converges to x , and x 2 n = (2 n ) 1 / (2 n ) = 2 1 /n n 1 /n = 2 1 /n x n . Taking the limit of both sides and recalling that 2 1 /n converges to 1, we arrive at x = x . Since x 1, the only viable solution is x = 1. #7) (a) (1 + 1 /n 2 ) n 2 is a subsequence of ((1 + 1 /N ) N ), which we know converges to e . Therefore, the sequence in question also converges to e . (b) ( (1 + 1 / 2 n ) 2 n ) is a subsequence of ((1 + 1 /N ) N ), which we know converges to e . Therefore, the subsequence also converges to e . Hence, ((1 + 1 / 2 n ) n ) = p (1 + 1 / 2 n ) 2 n e . (c) (1 + 1 /n 2 ) 2 n 2 = (1 + 1 /n 2 ) n 2 2 . So the sequence in question converges to e 2 by part (a) and the algebraic properties of limits. (d) There is no way to manipulate (1+2 /n ) n to get a subsequence of (1+1 /N ) N . By problem 5 (proven below), it suffices to show that the even-indexed and odd-indexed subsequences (1 + 2 / (2 k )) 2 k and (1 + 2 / (2 k- 1)) 2 k- 1 converge to the same thing. Even-indexed sequence: (1 + 2converge to the same thing....
View Full Document

This note was uploaded on 09/30/2009 for the course MATH 444 taught by Professor Junge during the Spring '08 term at University of Illinois at Urbana–Champaign.

Page1 / 3

solHMK6 - Section 3.4 #4) (a) x n = 1- (- 1) n + 1 /n . We...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online